(untitled) (CIPEEX, 2025)
ABSTRACT The use of botulinum toxin has driven further study of facial musculature, stimulating new approaches and treatment points. Current safe practice requires a dynamic assessment of aging and advanced anatomical mastery. The objective was to relate knowledge of facial musculature to the application of botulinum toxin. This was a narrative review. The search was performed in PubMed and Google Scholar, using the descriptors "Botulinum Toxin A," "muscles," "head," and "neck," combined by Boolean operators AND. Articles published between 2020 and 2025, in Portuguese or English, with free access, were included. Duplicate studies unrelated to the topic were excluded. Botulinum toxin blocks the release of acetylcholine at nerve endings, preventing muscle contraction and paralyzing the muscle by interrupting the transmission of electrical stimuli. Recent studies show that detailed anatomical knowledge of the facial muscles is essential for the safe application of botulinum toxin, avoiding complications such as asymmetries and eyelid ptosis, especially regarding the orbicularis oculi, corrugator supercilii, procerus, frontalis, levator labii superioris and alae nasi, levator labii superioris, zygomaticus minor and major, depressor septi nasi, depressor labii inferioris and anguli oris, masseter, and temporalis muscles. Safe practice also depends on recognizing individual anatomical variations and using the correct technique. This minimizes the risk of complications and achieves more natural aesthetic results. Conclusion Anatomical knowledge is essential to ensure the safety and satisfaction of procedures and is linked to constant updating in facial harmonization.